Estrategia de contenidos en Instagram para una cuenta de eduentretenimiento enfocada en bienestar emocional. Caso: nudos sueltos - Torres Bueno, Camila Valeria (2020)
This professional project consists of the content strategy that the author followed to position it as an Instagram account focused on emotional well-being, have a good reach, increase the growth of the account and generate a good engagement with her followers. The need for an audience niche for talking about their emotions and learning to live better with them was taken into account. For the realization, knowledge of branding, color theory, skills in graphic design, digital writing, intrapersonal and interpersonal communication, collaborations with other accounts and alliances with brands and related projects were applied. Regarding the strategy itself, the “Hashtag Blessed Instagram University” course by content creator and photographer Sorelle Amore was considered, a specialist in Digital Marketing was consulted and own experience has been a large part of the project as well. In addition, 8 interviews were conducted with followers who constantly interact with the account to find out their opinion about current and future content. It was possible to achieve a good brand positioning, aligned with its purpose, a great connection with the audience thanks to the honesty, enthusiasm and dedication behind each publication, a reach of 2,500 accounts per post, a constant growth of 5% in relation to the previous month and an engagement of 4.8% and 8.2% per post.